Promoting the urgency of restorative justice to environmental law enforcement officials through civic engagement education - Muhammad Karim Amrullah; Rr Dewi Anggraeni (Jurnal Cakrawala Pendidikan, 2023)
Although bringing cases of environmental damage to court means prioritizing the principle of primum remedium by way of retributive justice or criminal justice, it unfortunately creates various problems including the practice of corruption, collusion and nepotism. Therefore, it is necessary for law enforcement officials to understand and apply restorative justice in environmental crime, which means prioritizing the principle of ultimum remedium, through civic engagement education. This research method includes social research which also covers the field of law since it analyzes positive laws that are relevant to solving problems using literature and other sources as needed. This research uses a juridical-normative legal approach which is very dependent on the researcher's conception of positive law. The results of this study indicate that law enforcement officials should understand their position as part of the community members who have duties and authorities based on the law, so that justice and ecological goals can be achieved in efforts to preserve the environment.